RENEWABLE ENERGY IN THE CONTEXT OF ECONOMIC AND NATIONAL SECURITY THREATS UNDER RUSSIAN AGGRESSION - O. M. Гуменюк; I. I. Гуменюк (Подільський вісник: сільське господарство, техніка, економіка)
Renewable energy is a priority in making the “green” transition from climate-damaging fossil fuels to “clean” renewable energy sources, as well as ensuring sustainable access to energy worldwide. The article is aimed at analyzing the impact of the Russian-Ukrainian war on the development of renewable energy sources in Ukraine and its economic return. The authors suggest several effective low-cost steps to minimize the impact of the current Ukrainian situation on the economy and the formation of the energy independence of Ukraine, as well as the further development of the industry focused on quitting Russian gas.